The Potential of Electronic-Games In Harmonizing Differentiated Learning for Alpha Generation - Zakirman, Zakirman; Widiasih, Widiasih; Sukmayadi, Dodi; Aprianti, Rika; Nadiyyah, Khoirotun (FKIP - Universitas Riau, 2023)
The challenge of using rapid technology occurs in alpha generation learning activities, giving rise to differentiated learning. The variety of student learning styles is one of the benchmarks in differentiated learning so that supporting learning media in the form of electronic-games is needed. This study aims to describe the potential of electronic-games in harmonizing differentiated learning for generation alpha. This type of research is descriptive qualitative. Data collection techniques using questionnaires. The questionnaire was distributed online to respondents who were students of SMP Subulussalam Kota Padang Pariaman. The use of electronic-games in learning activities is one manifestation of differentiated learning. Differentiated learning views students differently and dynamically, where teachers see learning with various points of view. Novelty: Important contributions from the results of this research claim that the use of electronic games can support differentiated learning for the alpha generation.